Maternal malnutrition associated with postnatal sugar consumption increases inflammatory response and prostate disorders in rat offspring - Naia Fioretto, Matheus [UNESP]; Colombelli, Ketlin Thassiani [UNESP]; da Silva, Cecilia Luvizutti Ferreira [UNESP]; dos Santos, Sérgio Alexandre Alcantara [UNESP]; Camargo, Ana Carolina Lima [UNESP]; Constantino, Flávia Bessi [UNESP]; Portela, Luiz Marcos Frediani [UNESP]; Aquino, Ariana Musa de [UNESP]; Barata, Luisa Annibal [UNESP]; Mattos, Renato [UNESP]; Scarano, Wellerson Rodrigo [UNESP]; Zambrano, Elena; et al. (Elsevier, 2024)
Maternal malnutrition can alter developmental biology, programming health and disease in offspring. The increase in sugar consumption during the peripubertal period, a worldwide concern, also affects health through adulthood. Studies have shown that maternal exposure to a low protein diet (LPD) is associated with an increase in prostate disease with aging. However, the combined effects of maternal LPD and early postnatal sugar consumption on offspring prostate disorders were not investigated. The effects on aging were evaluated using a maternal gestational model with lactational LPD (6% protein) and sugar consumption (10%) from postnatal day (PND) 21–90, associating the consequences on ventral prostate (VP) rats morphophysiology on PND540. An increase was shown in mast cells and in the VP of the CTR + SUG and Gestational and Lactational Low Protein (GLLP) groups. In GLLP + SUG, a significant increase was shown in TGF-β1 expression in both the systemic and intra-prostatic forms, and SMAD2/3p had increased. The study identified maternal LPD and sugar consumption as risk factors for prostatic homeostasis in senility, activating the TGFβ1-SMAD2/3 pathway, a signaling pathway with potential markers for prostatic disorders.
Keywords: Inflammation; Maternal malnutrition; Prostate disorders; Sugar; TGFβ1-SMAD2/3